« A sociolinguistic study of insulting in Wolof, Seereer, Mandingo and Pulaar communities in Senegal » - Sarr, Ibrahima (Advances in Social Sciences Research Journal, 2019)
Sociolinguists have always tried to assess the relationship between language and society. In their works, however, some aspects of this relationship seem to be left to chance either because they are taboo or out of reach or are simply not interesting enough to them. What is undeniable is that one’s integration in a foreign community depends largely on one’s capacity to internalize the overall set of values. They also have to be careful not to overstep the bans. On the linguistic aspect, one of the most apparent of these bans is insulting; this is socially and morally shocking utterances meant to belittle the individual. This article focuses on the Senegalese society and seeks to highlight the sociolinguistic complexity of insulting. This implies an explicit definition of the concept, a study of its verbal and non verbal aspects, the semantic fields of insulting and its perception within society. Finally, we will study the factors that soften insults.